„Odnawia się młodość twoja jak orła” (Ps 103 [102], 5) . Motyw orła z krzyżem w dziobie na późnoantycznej tkaninie z Egiptu w kolekcji Władysława Czartoryskiego - Głowa, Anna (Vox Patrum, 2022)
The paper presents a formal analysis as well as an iconographic and iconological interpretation of the representation of an eagle on a little-known Late Antique textile from Egypt stored at the National Museum in Krakow. In the introduction, I outline the context of its origin, then move on to a formal analysis of the image decorating it and to indicate parallels both among textiles and other types of late antiquities from Egypt and Nubia. In order to understand the meaning of the eagle in the art of this era in general, and on textiles in particular, I first discuss, based on written and iconographic sources, the symbolism of this bird in the ancient and Early Christian world, and then the importance of decorations on clothing and household textiles in the late antiquity. The motif of the eagle and accompanying it attributes turns out to be a multidimensional symbol that can be read in various keys, illustrating the multiculturalism of the Late Antique world.